2006
DOI: 10.1029/2005ja011371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IMF BY on thermospheric composition at high and middle latitudes: 1. Numerical experiments

Abstract: [1] Magnetic storms and their effects on the thermosphere and ionosphere have been studied for many years, yet there are many aspects of the thermospheric and ionospheric responses that are not understood. The purpose of this paper is to show how the high-latitude composition depends on the sign of the IMF B Y component, using controlled simulations with a global first principles model. Because the high-latitude convection and neutral wind systems are strongly controlled by the IMF B Y component, it seems like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 47 publications
6
45
0
Order By: Relevance
“…Caspers and Prölss (1999) compared a selection of mass spectrometer latitudinal passes, at altitudes below 350 km, with the TIGCM modeling results of Crowley et al (1996) and Schoendorf et al (1996a,b), finding that the observations support the multiple cell patterns in the simulations, but that other interpretations of the data are possible. Crowley et al (2006) simulated northern hemisphere density at 140 and 200 km altitude using TIME-GCM with high-latitude convection patterns under different B y conditions. They found that the density cells at these altitudes rotated along with the convection pattern as B y changes from negative to positive.…”
Section: High-latitude Density Featuresmentioning
confidence: 99%
“…Caspers and Prölss (1999) compared a selection of mass spectrometer latitudinal passes, at altitudes below 350 km, with the TIGCM modeling results of Crowley et al (1996) and Schoendorf et al (1996a,b), finding that the observations support the multiple cell patterns in the simulations, but that other interpretations of the data are possible. Crowley et al (2006) simulated northern hemisphere density at 140 and 200 km altitude using TIME-GCM with high-latitude convection patterns under different B y conditions. They found that the density cells at these altitudes rotated along with the convection pattern as B y changes from negative to positive.…”
Section: High-latitude Density Featuresmentioning
confidence: 99%
“…[35] Figure 7 shows winds near a height of 250 km simulated by the Thermosphere Ionosphere Mesosphere Electrodynamics General Circulation Model (TIME-GCM) [Roble and Ridley, 1994;Crowley et al, 2006]. The results are for a geomagnetically quiet day (21 June 2004, daily Kp = 1), and were selected from the continuous four-year simulation described by Drob et al [2008].…”
Section: Scientific Applicationmentioning
confidence: 99%
“…Further corrections for solar EUV flux variations use daily measured solar 10.7‐cm radio flux as a proxy for solar EUV. DE‐1 images in this and the accompanying report [ Crowley et al , 2006] are only shown after the application of this processing technique.…”
Section: Global Fuv Observationsmentioning
confidence: 99%
“…It is run with the above‐specified inputs over the time frame beginning on Day 263 (20 September), 1981 and finishing at the end of Day 284 (11 October). This interval covers the two event intervals beginning on Days 267 and 280 discussed by Immel et al [1997] and noted by Crowley et al [2006]. Starting the run several days before the first event interval and running it continuously on through the second interval allows the TIMEGCM to best simulate the atmospheric conditions existing prior to the onset of significant magnetic activity.…”
Section: Timegcm Model Runs and Analysis Techniquementioning
confidence: 99%